South China Sea arbitration: legal and geopolitical implications of an unenforceable arbitral award - Freidenfelds, Pauls (Riga Graduate School of Law, 2018)
The thesis is about historical development of the South China Sea conflict. Author analyses the legal issues of the ruling by providing analysis of the legal implications and enforcement of the arbitral by the PCA in case of the Philippines v. China in correlation with how China’s rejection of the ruling impacts the existing international legal order. The following three main research questions are addressed and answered in the paper: 1) what are the possible legal implications of the arbitral award in the case of the Philippines v. China? 2) why it is not possible to enforce China to comply with the ruling by the Permanent Court of Arbitration? 3) how does the ruling impact international geopolitical situation?
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International private law and international procedural law; International arbitration; International arbitral awards